Sustainability and resilience in midwifery: A discussion paper. (September 2016) - Crowther, Susan; Hunter, Billie; McAra-Couper, Judith; Warren, Lucie; Gilkison, Andrea; Hunter, Marion; Fielder, Anna; Kirkham, Mavis
Abstract: Background: midwifery workforce issues are of international concern. Sustainable midwifery practice, and how resilience is a required quality for midwives, have begun to be researched. How these concepts are helpful to midwifery continues to be debated. It is important that such debates are framed so they can be empowering for midwives. Care is required not to conceptually label matters concerning the midwifery workforce without judicious scrutiny and diligence. Aim: the aim of this discussion paper is to explore the concepts of sustainability and resilience now being suggested in midwifery workforce literature. Whether sustainability and resilience are concepts useful in midwifery workforce development is questioned. Method: using published primary midwifery research from United Kingdom and New Zealand the concepts of sustainability and resilience are compared, contrasted and explored. Findings: there are obvious differences in models of midwifery care in the United Kingdom and New Zealand. Despite these differences, the concepts of resilience and sustainability emerge as overlapping themes from the respective studies' findings. Comparison between studies provides evidence of what is crucial in sustaining healthy resilient midwifery practice. Four common themes have been identified that traverse the different models of care; Self-determination, ability to self-care, cultivation of relationships both professionally and with women/families, and a passion, joy and love for midwifery. Conclusions: the impact that midwifery models of care may have on sustainable practice and nurturing healthy resilient behaviors remains uncertain. The notion of resilience in midwifery as the panacea to resolve current concerns may need rethinking. Resilience may be interpreted as expecting midwives 'to toughen up' in a workplace setting that is socially, economically and culturally challenging. Sustainability calls for examination of the reciprocity between environments of working and the individual midwife. The findings invite further examination of contextual influences that affect the wellbeing of midwives across different models of care. Highlights: What sustains midwifery practice and how resilience is a quality required in practice have begun being researched. Models of care that focus on relationships have been shown to be beneficial to mothers, families and midwives. This paper explores and critiques the notions of sustainability and resilience as applied to midwifery. This paper begins to examine the notions of resilience and sustainability across very different models of midwifery care. Four main qualities/themes that traverse two models of midwifery care are identified and discussed: Love, passion and joy of midwifery, self-care, self-determination and relationships sustain.